2021
DOI: 10.1186/s12879-021-06888-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcriptomics biomarkers for the early prediction of the prognosis of septic shock from pneumopathies

Abstract: Background Identifying the biological subclasses of septic shock might provide specific targeted therapies for the treatment and prognosis of septic shock. It might be possible to find biological markers for the early prediction of septic shock prognosis. Methods The data were obtained from the Gene Expression Omnibus databases (GEO) in NCBI. GO enrichment and KEGG pathway analyses were performed to investigate the functional annotation of up- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Furthermore, according the microarray analyses by Ye et al [12], THBS1 was downregulated in SAT patients and could be served as the prognostic marker for sepsis with pneumonia. Shi et al also con rmed the downregulation pattern of THBS1 in septic shock and showed it could serve as differentiation factor with high AUC of 0.889 [13]. Here, we established the mouse SAT model by LPS induction, and found that THBS1 is signi cantly in LPS challenged mice decreased compared to the control mice, which is preliminary con rmed that the involvement of THBS1 in the presence of SAT.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, according the microarray analyses by Ye et al [12], THBS1 was downregulated in SAT patients and could be served as the prognostic marker for sepsis with pneumonia. Shi et al also con rmed the downregulation pattern of THBS1 in septic shock and showed it could serve as differentiation factor with high AUC of 0.889 [13]. Here, we established the mouse SAT model by LPS induction, and found that THBS1 is signi cantly in LPS challenged mice decreased compared to the control mice, which is preliminary con rmed that the involvement of THBS1 in the presence of SAT.…”
Section: Discussionsupporting
confidence: 74%
“…However, in dataset, since no differential genes were screened out with adj. p .val < 0.05 ( Table S4 ), and the p -value < 0.05 is also allowed in the bioinformatics analysis ( Cheng et al, 2021 ; Shi et al, 2021 ), we use p .val < 0.05 & log |FC | > 1.5 as the cutoff. Performance of the model was evaluated through timeROC package (v0.4).…”
Section: Methodsmentioning
confidence: 99%
“…Omics, cell surface marker expression, immune cell profiles, and biomarker analysis have been utilized to classify the immune status of sepsis patients (10,12,(14)(15)(16)(17)(18)(27)(28)(29). However, no studies have examined how these omic changes correlate with fundamental mechanisms of neutrophil-mediated damage in sepsis, specifically how heterogeneous neutrophil-endothelial cell interactions differentially impact vascular barrier disruption and neutrophil migration across the endothelium into vital organs.…”
Section: Introductionmentioning
confidence: 99%